Migrants’ narratives on urban governance: a case from Kolkata, a city of the global south - Chakrabarti, A.; Tiwari, Reena; Banerji, H. (MDPI, 2021)
The paper aims to reveal the politics of urban governance and the associated impact on the lives of disenfranchised migrants. It critically explores the urban governance structure and the nature of practices involved in the cycle of settlement, eviction, resistance and resettlement. The case of Nonadanga, located at the urban margin of Kolkata, India, was explored for this purpose. An ethnographic methodology comprising observation, semi-structured interviews and oral history was adopted for the research. Twelve squatter dwellers and four experts working in Nonadanga and Kolkata were interviewed for this purpose. A three-step data analysis comprising a narrative approach, thematic network analysis and validation was adopted. A critical review of inclusive practices, together with ethnographic survey findings, demonstrates that migrants live in a condi-tion the paper calls “partial rights”, which is a manifestation of the dialectics of inclusiveness prac-ticed by the urban governance structure and derived from the interaction between urban governance structure and migrants’ agency. By analyzing past development trends, the paper outlines possible future scenarios for migrants’ living conditions and discusses their impact on achieving the targeted Sustainable Development Goal 11 for inclusive cities by 2030.